PELATIHAN â€œSINERGI Iâ€ MENINGKATKAN KEMAMPUAN PROSOSIAL REMAJA - Ekawati, Dian; Martani, Wisjnu (Faculty of Psychology, Diponegoro University, 2013)
Prosocial capability is important for adolescents, because it can be function as a protective factor against risky behaviors. The purpose of this study is to examine improvements in pro-social capability of adolescents aged 14-16 years old in post training delivery SINERGI I training program. Helpfulness and other-oriented empathy are aspects that trained by using the concept of experiential learning as well as methods of games, discussion, reflection, and role-playing. Participants for the experimental group and control group derived from different schools. The number of participants is 15 students in the experimental group and 15 students in the control group. A quasi-experimental method with the untreated control group design with dependent pretest and posttest samples was used in this study. Adolescentâ€™s pro-social capabilities measured by the pro-social scale of PPB (Prosocial Personality Battery) with 14 items and alpha reliability of 0.856. The hypothesis of this study is the â€œSINERGI Iâ€ training program could improving adolescentâ€™s pro-social capability. Quantitative data analysis were using a parametric t-test and analysis of variance (ANOVA). The results of quantitative analysis of gained score experimental and control groups showed significant differences with t = 2.351; p = 0.30 (p â‰¤ 0.05). while for ANOVA obtained F = 5.866, p = 0.026 (p â‰¤ 0.05). This result suggests that SINERGI I program could improve adolescentâ€™s pro-social capability.